Fibrous oil palm frond as a potential microbial immobilization carrier for enhanced 1,3-propanediol productivity - Tey, Ker Yee; Luthfi, Abdullah Amru Indera; Abdul Manaf, Shareena Fairuz; Mong, Guo Ren; Woon, Kok Sin; Yeap, Swee Keong; Mahmod, Safa Senan; Jamali, Nur Syakina; Tan, Jian Ping (Elsevier, 2024)
In line with Sustainable Development Goal 12: Responsible Consumption and Production, the biotransformation of crude glycerol into 1,3-propanediol establishes a circular bioeconomy between regional crude glycerol and value-added green polymer. However, the bioproduction of 1,3-propanediol is restricted by a slow conversion rate, which could potentially be overcome using the immobilization technique. In this work, the locally isolated Clostridium butyricum JKT 37 was immobilized on coconut shell activated carbon (CSAC), granular durian peel (GDP), or fibrous oil palm frond (FOPF) to ferment crude glycerol to produce 1,3-propanediol. Amongst these, the immobilized cell density of FOPF was four times higher than the CSAC. FOPF immobilizer had resulted in an improvement in the immobilization efficiency (45.61 %), 1,3-PDO productivity (22.93 %), and maximum instantaneous productivity (36.12 %) as compared to the CSAC. 18.99 g/L of 1,3-PDO was produced from immobilized-FOPF fermentation at the highest yield of 0.65 mol/mol. This superior cell adsorption on FOPF was supported by its high water absorption index (4.16 g/g) and morphology. GDP immobilizer had a higher immobilized cell density (9.20 g/L) and cell retention (0.18 g/g) than CSAC, with insignificant improvement in the 1,3-propanediol production. The biological activity of the immobilized cells on FOPF was validated in 12 cycles repeated batch fermentations with 1,3-PDO yield and productivity as high as 0.68 mol/mol and 1.43 g/L.h, respectively. This research has proven the high performance of fibrous immobilizers and serves as the benchmark for future investigation into the use of agricultural waste to enhance other bioprocess's productivity.